Sistem Informasi Pelaporan Kekerasan Perguruan Tinggi Berbasis Web dengan Mekanisme Keamanan Akses dan Tracking Status Mandiri: Web-Based Higher Education Violence Reporting Information System with Access Security Mechanisms and Self-Service Status Tracking - Shafira Dwi Nur'izzati; Mohammad Humam; Bayu Aji Santoso (Jurnal Informatika dan Multimedia, 2026)
This study presents the development of a web-based PPKPT Reporting and Case Management Information System using the Waterfall method at Harkat Negeri University. Violence in higher education settings is a serious issue, yet current reporting mechanisms rely solely on WhatsApp messages, failing to guarantee reporter identity confidentiality, structured case management, or independent case status tracking. The system was developed using the Waterfall SDLC model, the Laravel framework, and a MySQL database, modeled with UML. It features online reporting with identity confidentiality enforced through AdminAuth middleware authentication, a status-tracking mechanism using a unique code (PPKPT-YYYY-XXXXX), an admin dashboard, report management, and PDF export. Black Box Testing on 22 test cases produced a 100% pass rate, confirming all features function as specified. User Acceptance Testing (UAT) with 20 respondents consisting of 3 PPKPT Team members, 1 lecturer, 1 administrative staff, and 15 students yielded an overall mean score of 4.51 (Very Good category), with no aspect scoring below 2.60. The system successfully integrates three core components in a single platform: reporting with identity access control protection, structured case management for the PPKPT Team, and independent status tracking for reporters — components mandated by Permendikbudristek No. 55 of 2024 that had not previously been integrated into any single system designed for a higher-education PPKPT context.